Return Portofolio Optimal Menggunakan Single View Black-litterman Model dengan Pendekatan ARIMA (Autoregressive Integrated Moving Average) - Adri Arisena; Sugiyanto Ikhsan (Jurnal Co Management, 2019)
At this time stock investment is one investment option. To obtain optimal profits a stock portfolio is needed. A portfolio is a combination of several shares. To form a portfolio, a model is needed to achieve an optimal portfolio. This research uses Single View Black-Litterman Model with ARIMA (Autoregressive Integrated Moving Average) approach. The selected shares are PT. Jasa Marga (JSMR), PT. Unilever Indonesia (UNVR), and PT. Waskita Karya (WSKT).